Pendekatan Value Engineering untuk Optimasi Proses Pemilihan Material - Lydiawati Soelaiman (Universitas Bunda Mulia, 2017)
Value Engineering is far more than a means of simply reducing existing costs. This method can be delineating alternatives and to suggest choices based on the necessity of the function based on cost-worth relationship. The principles of Value Engineering can be applied by any sectors as a management tool to control costs. In this case, Value Engineering is used in construction industry to optimize material selection process. Based on its function, the study put local ceramic from some brands. The output shows rank of criteria based on the floor function determine by respondents. Further analysis with decision matrix gives recommendation of the best value from several ceramic brands.Keywords: Value Engineering, Material Selection Process, Ceramic Floor